2020
DOI: 10.3390/cancers12113249
|View full text |Cite
|
Sign up to set email alerts
|

Poziotinib Inhibits the Efflux Activity of the ABCB1 and ABCG2 Transporters and the Expression of the ABCG2 Transporter Protein in Multidrug Resistant Colon Cancer Cells

Abstract: Colorectal cancer (CRC) is a leading cause of cancer deaths in the United States. Currently, chemotherapy is a first-line treatment for CRC. However, one major drawback of chemotherapy is the emergence of multidrug resistance (MDR). It has been well-established that the overexpression of the ABCB1 and/or ABCG2 transporters can produce MDR in cancer cells. In this study, we report that in vitro, poziotinib can antagonize both ABCB1- and ABCG2-mediated MDR at 0.1–0.6 μM in the human colon cancer cell lines, SW62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 79 publications
2
15
0
Order By: Relevance
“…The reduction in paclitaxel-induced ATPase activity in vitro when lapatinib or poziotinib are present demonstrates physical interference with ABCB1 function. Our results are in agreement with others that have proposed a mechanism whereby TKIs, including lapatinib and poziotinib, physically bind to and inhibit ABCB1 rendering the transporter non-functional [ 27 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reduction in paclitaxel-induced ATPase activity in vitro when lapatinib or poziotinib are present demonstrates physical interference with ABCB1 function. Our results are in agreement with others that have proposed a mechanism whereby TKIs, including lapatinib and poziotinib, physically bind to and inhibit ABCB1 rendering the transporter non-functional [ 27 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Others have previously reported synergistic antitumor activity using paclitaxel and lapatinib in combination for esophageal and ovarian cancer [ 31 , 32 ]. To our knowledge, this is the first report of anticancer synergy using poziotinib in combination with paclitaxel in ovarian cancer, although poziotinib-mediated inhibition of ABCB1 activity was recently reported in colon cancer cells [ 33 ]. Both poziotinib and lapatinib are TKIs that primarily target ErbB protein tyrosine kinases EGFR, ERBB2, and ERBB4 [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The varying expression levels of ABC transporter genes are responsible for drug resistance in many chronic diseases and cancer [19]. Up-regulation of many kind of ABC transporters, including ABCB1 and ABCG2 leads to diminished cellular drug efflux [20]. Compatible with this fact, in this current study, we found significantly changed expression levels of ABC genes in the CP group.…”
Section: Discussionsupporting
confidence: 61%
“…Till now, tremendous efforts have been made to explore the mechanism of MDR, mostly by establishing ABC transporter-overexpressing cancer cell lines (9,29). By comparing parental and resistant cancer cell lines using molecular biology and cellular methods, researchers have identified numerous ABC transporter substrates (21,(30)(31)(32)(33)(34) as well as inhibitors (16,(35)(36)(37)(38)(39)(40). Computational strategies were also developed to boost the modulator discovery process especially multitarget modulators (41,42).…”
Section: Discussionmentioning
confidence: 99%